2018
DOI: 10.3389/fpubh.2018.00254
|View full text |Cite
|
Sign up to set email alerts
|

Exit-Knowledge of Ambulatory Patients About Medications Dispensed in Government Hospital in Eastern Ethiopia: The Need for Focused Patient Counseling

Abstract: Background: In the counseling process, a multi-cultural competence of dispenser is among the key factors affecting his/her successful communication with patients for achieving optimal use of medications. For patients to use dispensed drugs appropriately, it is a must for them to understand the medication related information provided by the dispenser. Hence, the objective of this study was to identify parameters that likely affect ambulatory patients' knowledge of medication(s) provided at the exit of outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 18 publications
1
26
3
Order By: Relevance
“…18,27 Overall, 81% of patients had sufficient exit-knowledge regarding their dispensed medications. This finding was higher than the studies conducted; in Eastern Ethiopia 38.6% 26 and in Hiwot Fana University Specialized Hospital 46%. 27 Additionally, a study conducted in Gondar, Ethiopia revealed that 38.3% of patients were found to have good knowledge on their medications 25 and a study from the rural Gambia showed that 16.1% of patients had good knowledge on their dispensed drugs.…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…18,27 Overall, 81% of patients had sufficient exit-knowledge regarding their dispensed medications. This finding was higher than the studies conducted; in Eastern Ethiopia 38.6% 26 and in Hiwot Fana University Specialized Hospital 46%. 27 Additionally, a study conducted in Gondar, Ethiopia revealed that 38.3% of patients were found to have good knowledge on their medications 25 and a study from the rural Gambia showed that 16.1% of patients had good knowledge on their dispensed drugs.…”
Section: Discussioncontrasting
confidence: 61%
“…Our finding is relatively comparable with a study conducted in Eastern Ethiopia, which showed that majority of the participants (89.2%, 82.5%, 72.3%, 63%, 54.9%, and 54.7%) recalled frequency, route, medication instruction, expected therapeutic outcome, proper storage conditions, and drug interactions, respectively. 26 Likewise, the study from Eastern Ethiopia revealed that 37.2%, 37.2%, and 28.7% recalled the name, major side effects, and actions to be taken when a dose is omitted, respectively. In the same way, our finding showed that less than half of the participants recalled the name (44.5%) and major side effects (31.2%) of their dispensed medications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations